Elementary education in India versus China: Guidelines for NEP implementation - Naveen Kumar; Vinitha Varghese (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper documents the state of elementary education in India and China since the 1960s, key lessons for India from China's shift in focus from 'quantity' to 'quality', and evidencebased guidelines for effective implementation of India's New Education Policy 2020 (NEP 2020). The divergent policy focus has led to differential trajectories for elementary education in the two emerging economies, with China being decades ahead in improving literacy rates. China's adoption of the New Curriculum Reform 20 years before India's NEP 2020 has put China on the path to achieving equitable development of 'quality' compulsory schooling. India's NEP 2020 has components that have the potential to improve quality, equity, and efficiency of the education system. This paper makes the following recommendations for effective implementation of some of the NEP 2020 components: (1) an additional worker should be recruited at every preschool centre; (2) more resources should be allocated towards implementation, evaluation, and needed recalibration of the management of school clusters; (3) teacher recruitment, training, and rewards should be revamped; (4) standardized tests should be protected from data corruption, fudging, or grade inflation; and (5) a national-level road map and regular evaluations have to be introduced to ensure participation of socio-economically disadvantaged groups in education.
Keywords: I21; I24; I28; I38; 330; education; schooling; quality; India; China